Research on SDN based tactical communication network architecture - Tai LIU; Chao ZHU; Yi CHENG; Yiming WANG (Dianxin kexue)
Tactical communication networks has high dynamic, weak connection, low bandwidth, multi-link backup, SDN (software defined network) technology decouples from hardware and software through traditional network control devices, software the core control functions, get a global view through centralized control policies, so as to realize the flexible scheduling of resources and the efficient utilization of channel resources, promote the development of tactical communication networks more intelligent and flexible adaptive.The development status and advantages of software defined network were firstly introduced, the problems of traditional architecture of tactical communication networks were analyzed, including the application of SDN in the field of foreign military tactical communication.Then, the feasible idea of the application of SDN in the field of military communication was put forward, as well as the application scenarios were conceived.Finally, the feasibility of the application of SDN in military communication was summarized.